2015
DOI: 10.1016/j.ijms.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Competitive hydrogen atom migrations accompanying cascade dissociations of peptide cation-radicals of the + type

Abstract: We report a combined experimental and computational study of energy-resolved collision-induced dissociation (ER-CID) and time-resolved infrared multiphoton dissociation (TR-IRMPD) of z4 ions prepared by electron transfer dissociation of peptide (Ala-Ala-Asn-Ala-Arg + 2H)2+ ions. The z4 cation-radicals, •ANAR+, undergo competitive dissociations by backbone cleavage and loss of a CONH2 radical from the Asn side chain. The backbone cleavage proceeds by radical-assisted dissociation of the Asn Cα—CO bond, forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The transition state energy for the Ala-2-H  migration (TS1, 109 kJ mol -1 , Table 1) was very similar to TS energies for analogous H  migrations reported previously for • ANAR + , • ASAR + , and • ATAR + peptide z ions (100-123 kJ mol -1 ) [48,69], indicating that these reactions share common features regarding electronic and steric factors affecting the TS energy. The subsequent CO-NH bond dissociation in the cis-Ala-2--radical 3 can proceed through TS2 at 138 kJ mol -1 relative to 1.…”
Section: Structures and Energies Of Z 4 Ionssupporting
confidence: 81%
“…The transition state energy for the Ala-2-H  migration (TS1, 109 kJ mol -1 , Table 1) was very similar to TS energies for analogous H  migrations reported previously for • ANAR + , • ASAR + , and • ATAR + peptide z ions (100-123 kJ mol -1 ) [48,69], indicating that these reactions share common features regarding electronic and steric factors affecting the TS energy. The subsequent CO-NH bond dissociation in the cis-Ala-2--radical 3 can proceed through TS2 at 138 kJ mol -1 relative to 1.…”
Section: Structures and Energies Of Z 4 Ionssupporting
confidence: 81%
“… 293 Additionally, Turacek and colleagues have used radical product ions, created via ETD, to extensively study structure and ion chemistry of peptides with a variety of approaches for theoretical and analytical purposes. 294 300 …”
Section: Other Uses Of Etd and Related Ion–ion Reactionsmentioning
confidence: 99%
“…The N–C α bond cleavages can also lead to the generation of [z n −1 + H] •+ species via either the peptide radical cation directly or the fragment ion [x n −1 + H] •+ , involving a β‐radical–driven N–C α bond‐cleavage process . The c/z‐type ions can also be produced from hydrogen‐rich peptide radical cations [M + n H] •( n −1)+ generated using ECD or ETD . Theoretical investigations have suggested that an aminoketyl radical intermediate would form and undergo a homolytic cleavage of the adjacent N–C α bond to give an ion–molecule complex .…”
Section: Radical–induced Fragmentation Of Peptide Radical Cationsmentioning
confidence: 99%